Novel Metal Coordination Complexes Based on 4-Aminophenol: Spectroscopic Analysis and Antibacterial Test - Husna Syaima; Sentot Budi Rahardjo; Anisa Nurul Hanifa; Ariffah Ana Fathonah; Ratna Setyaningsih (Indonesian Journal of Chemistry, 2023)
The aims of this research are to synthesize and determine the formula, characteristics, and complex structure of Cu(II) and Co(II) with 4-aminophenol and to investigate their antibacterial activity. The complexes were synthesized by refluxing a solution of CuSO4·5H2O and CoSO4·7H2O, respectively, with 4-aminophenol in methanol for 1 h. The products were characterized using UV-Vis spectroscopy, atomic absorption spectroscopy, thermal analysis, conductivity, FTIR, and magnetic moment. The formation of the complex was indicated by shifting of maximum wavelength of the metal solution toward shorter, i.e., 817  to 421 nm for Cu(II) and 566  to 450 nm for Co(II). From the characterization, the proposed formulas of the complexes are [Cu(4-aminophenol)4]SO4 and [Co(4-aminophenol)4(H2O)2]SO4·5H2O forming square planar and octahedral geometry, respectively. Both complexes are paramagnetic with negligible antibacterial activity against Staphylococcus aureus, Staphylococcus epidermis, Escherichia coli, and Pseudomonas aeruginosa.